Study on Relationship among Oil Content, Fatty Acid Composition and Seed Characters of Diploknema butyracea - B. B. Bandyopadhyay (Current Topics in Agricultural Sciences Vol. 2, 2021)
Diploknema butyracea (Phulwara/cheura plant) grows in wild form in sub-Himalayan tracts and outer Himalayan ranges of Uttarakhand state. The plant contains high concentration (> 60%) of oils/fats in kernel along with high palmitic acid (56.80 - 64.10%), oleic acid (28.00 – 31.30%), linoleic acid (4.30 - 5.70%) and stearic acid (2.40 – 3.50%). Oil/fat is used for edible purposes and for preparation of local medicine, soap, etc. Conventional approaches of breeding are difficult for the improvement of plant because of recalcitrant types of seed and perennial nature of growth habit. There has a need to harness the quantity and quality control of oil in crop through selection of superior genotypes based on its fatty acid compositions in seeds and on seed characters as morphological marker traits of plant species. In this investigation correlation and path coefficient study was performed among 4 major fatty acid components, total fat/oil content and some seed characters. The results revealed that palmitic acid, stearic acid and seed coat colour determined the oil content in kernel. Non-significant relation between total fat/oil content and other traits emerged from negative influence of oleic acid, linoleic acid and other fatty acid in opposite direction.